Occupational stress and coping strategy among community health workers of Mangalore Taluk, Karnataka - Santosh Aryal; Mackwin Kenwood D'mello (Wolters Kluwer Medknow Publications, 2020)
Background: Understanding the stress related to work among community health workers (CHWs) might be beneficial to plan intercessions to draw in and spur health-care professionals to toil in remote and disadvantaged region as well as to guarantee the quality of care. Objectives: This study was conducted to determine the prevalence, level, and sources of occupational stress among CHWs and coping strategies adopted by the CHWs. Methods: This cross-sectional study was conducted from January to April 2019 among 347 CHWs in 16 Primary Health Centres of Mangalore taluk, Karnataka. Occupational Stress Index and the Brief COPE scale were used to assess the stress level and coping strategy, respectively. Descriptive statistics and Chi-square test were used. The P = 0.05 was considered as significant. Results: The prevalence of occupational stress was found to be 40.5%. Stressors such as under participation, powerlessness, low status, and unprofitability were significantly associated with occupational stress. CHWs used various coping strategies such as self-distraction, active coping, denial, substance use, behavioral disengagement, venting, positive reframing, humor, and self-blame to manage their stress. Conclusion: Stress intercession programs could be conducted on a regular interval to make CHWs "stress-free". Higher stress level might impede the performance of the workers, and hence addressing this is necessary. Similarly, positive coping strategies, such as active coping, should be promoted to manage stress.